The role of PET/CT in radiotherapy for nasopharyngeal carcinoma - Li, Hongjia; Kong, Ziren; Xiang, Yongbo; Zheng, Rong; Liu, Shaoyan (Frontiers in Oncology, 2022)
Radiotherapy has already been developed as the standard of care for patients with nasopharyngeal carcinoma (NPC), and precision staging, target volume delineation, prognosis prediction, and post-treatment surveillance are essential in the management of NPC. Positron emission tomography/computed tomography (PET/CT) is increasingly recognized as an imaging modality to guide precision radiotherapy in these areas. The feasibility and efficacy of 18F-FDG PET/CT have been confirmed in tumor diagnosis, treatment planning, prognosis, surveillance, and assessment. Coupled with the capability of revealing tumor metabolic information, 18F-FDG PET/CT is more accurate in identifying primary lesions and metastases of NPC than other conventional imaging methods including CT and MRI and shows the independently diagnostic and prognostic value for radiotherapy. However, 18F-FDG has limitations due to its physiological distribution in brain tissue and increasing uptake in post-radiation inflammation. Novel PET radiotracers including FAPI, NaF, CHO, and FLT are explored as alternatives with potential superiority for radiotherapy in NPC. In this review, we summarized the evolving role of PET/CT in the management of radiotherapy in NPC patients, aiming to facilitate precision radiotherapy from a molecular imaging aspect.